Approach to design method for micro-scale landscape in hot and humid climate: a case study of new housing area in Johor, Malaysia - saito, Kei; Said, Ismail; Rasidi, Hisyam; Shinozaki, Michihiko (University Alam Bina, Lecturers, 2010)
The purpose of this study is to address a micro-scale environmental-friendly landscape design methods in consideration of hot and humid climate with a combination of spatial data and physical environmental data in the new residential area in Johor, malaysia. In this study, we showed research achievements so far as a first step as follows. 1. literature review has cleared current research situation and necessity of effective investigation for environmental-friendly design methods in Malaysia. 2. We have gathered relevant spatial and climate observation data and improved data format for integrated database to develop the GIS (Geographic Information System) environment for quantitative spatial analysis. 3. Several candidate design elements for the next step investigation became clear through the physical comparative study of the target sites using GIS-generated thematic maps.